2022
DOI: 10.1051/0004-6361/202244719
|View full text |Cite
|
Sign up to set email alerts
|

A lensed protocluster candidate at z = 7.66 identified in JWST observations of the galaxy cluster SMACS0723−7327

Abstract: Context. According to the current paradigm of galaxy formation, the first galaxies likely formed within large dark matter haloes. The fragmentation of these massive haloes led to the formation of galaxy protoclusters, which are usually composed of one to a few bright objects, surrounded by numerous fainter (and less massive) galaxies. These early structures could have played a major role in reionising the neutral hydrogen within the first billion years of the Universe, especially if their number density is sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 59 publications
3
5
0
Order By: Relevance
“…Our estimated lower limit of the mass of A2744-z7p9OD is comparable to those of previously known protoclusters and protoscluster candidates using similar methods, including the recently reported candidate behind the SMACS0723 cluster (Laporte et al 2022), where two of the member candidates are spectroscopically confirmed to be z = 7.66. The real breakthrough of our observations, however, is the sheer number of spectroscopically confirmed redshift measurements, which allow us to establish secure membership to the protocluste and get a first estimate of the its velocity dispersion.…”
Section: Comparison With Previous Worksupporting
confidence: 84%
See 1 more Smart Citation
“…Our estimated lower limit of the mass of A2744-z7p9OD is comparable to those of previously known protoclusters and protoscluster candidates using similar methods, including the recently reported candidate behind the SMACS0723 cluster (Laporte et al 2022), where two of the member candidates are spectroscopically confirmed to be z = 7.66. The real breakthrough of our observations, however, is the sheer number of spectroscopically confirmed redshift measurements, which allow us to establish secure membership to the protocluste and get a first estimate of the its velocity dispersion.…”
Section: Comparison With Previous Worksupporting
confidence: 84%
“…Second, we attempt to estimate the mass of the structure. Following previous work (e.g., Laporte et al 2022), we can estimate the halo mass of the individual components from the halo-mass-galaxy-luminosity relation. Using the relation derived by Mason et al (2022), we infer that the brightest member of the overdensity (ZD2, M UV = −20.1) lives in a M h ≈ (7 ± 2) × 10 10 M e halo.…”
Section: Discussionmentioning
confidence: 99%
“…(e.g., Castellano et al 2022, Roberts-Borsani et al 2022. The origin of the ionizing photons that produce these ionized bubbles is still highly debated and could be either due to the intrinsic nature of the object (e.g., star formation or an active galactic nucleus) or the overdense environment near the most-massive galaxies formed at high redshift (Leonova et al 2021;Laporte et al 2022). Indeed previous research into these galaxies indicates that they reside within ionized bubbles, large enough that any blue peak escaping the host galaxy would be redshifted past the Lyα line center before leaving the ionized bubble and hence should be unaffected by IGM absorption.…”
Section: Targets Selectionmentioning
confidence: 99%
“…Exploring massive structures in the highredshift universe can unveil their origin. In recent decades, protoclusters, which are progenitors of local clusters with halo mass of ( )  > M M log 14 halo , have been found out to z ∼ 7-8 (e.g., Harikane et al 2019;Hu et al 2021;Laporte et al 2022). They have often been found through the overdensity of starforming galaxies, such as bright galaxies in rest-frame ultraviolet continuum (e.g., Steidel et al 1998;Overzier et al 2008;Toshikawa et al 2018), Lyα emission (e.g., Shimasaku et al 2003;Jiang et al 2018;Harikane et al 2019), Hα emission (e.g., Hayashi et al 2012;Darvish et al 2020), and infrared (e.g., Miller et al 2018;Oteo et al 2018).…”
Section: Introductionmentioning
confidence: 99%